Study on lateral stability control of carrier-based aircraft towbarless tractor system - Jiyan Qi; Haoyang Xu; Ming Su (Systems Science & Control Engineering)
The lateral stability and control of carrier-based aircraft towbarless tractor system are analysed. Considering the coupled motion effects of carrier roll, pitch and heave, a four degree of freedom time-varying nonlinear dynamic model of the carrier-based aircraft towbarless tractor system is established. The lateral stability of the traction system is analysed, and the discrimination method of the system instability form is proposed. The yaw rate of the tractor and the lateral speed of the carrier-based aircraft are selected as variables, the lateral stability controller is designed using sliding mode control (SMC) theory and the compensation torque and lateral force required for the lateral stability control of the traction system are obtained, thereby achieving tracking of the ideal values. The simulation results show that the designed control scheme can effectively controls the yaw rate of the target tractor and the lateral speed of the carrier-based aircraft, ensuring the lateral stability of the carrier-based aircraft towbarless tractor system.